Diskulakization and forced relocation of kulaks (on the example of The Kabardino-Balkar auton-omous region) - Alim I., Tetuev (Kavkazologiya, 2025)
The article examines the system of dispossession and forced eviction of kulaks in the Kabardino-Balkarian Autonomous Region. The article examines the legal framework for the administrative and forced eviction of kulaks. The reasons, number and procedure for administrative eviction of third-category kulaks within the North Caucasus Region are determined. The features of socio-economic development on the eve of the complete collectivization of mountainous and lowland areas of the region are revealed. The reasons, procedure for dispossession and the number of evicted wealthy peasants are established. The reasons and consequences of peasant protests are determined. The system of political repression is examined. It is concluded that political repres-sions were caused by the establishment of an authoritarian regime of power in the center and lo-cally and were used to solve political, socio-economic problems.